IDENTIFIKASI MANGROVE SEBAGAI SUMBER ANTIOKSIDAN DI ECOWISATA CUKU NYINYI DESA SIDODADI PESAWARAN PROVINSI LAMPUNG - Oktaf Rina; Dara Aditya; Susilawati, Susilawati; Erdi Suroso; Hamdani, Hamdani; Ajis Purnomo; Andi Sofiyan (Jurnal Cakrawala Ilmiah, 2024)
Mangrove plants are located in Pesawaran district which has an area of around 113 hectares. This activity was empowerment community programme assisted by PT. Bukit Asam Tbk Pelabuhan Tarahan Lampung. This research used 3 types of mangroves, namely Rhizophora apiculata, Rhizophora mucronata, and Rhizopora stylosa. The three types of mangrove fruit were taken for testing three times. The resulting data obtained will be presented descriptively in the form of tables and graphs. to find out the differences between the three mangrove fruits. The research results showed that the types of Rhizopora stylosa, Rhizopora mucronata, and Rhizopora apiculata contained flavonoid, saponin and phenolic compounds in phytochemical analysis. However, the apiculate was negative type contains triterpenoid and steroid compounds. The best antioxidant power based on the best IC50 measurement is 178.45 ppm for the Rhizopora stylosa type, Rhizopora mucronata has an antioxidant power of 922.82 ppm, and Rhizopora apiculata has an antioxidant power of 731.10 ppm.